Da necessidade do legislador na obra Do contrato social, de Jean-Jacques Rousseau - Souza, Felipe Araújo de [UNESP] (2016)
The figure of the Legislator in The Social Contract work of Jean-Jacques Rousseau comes amid a popular form of legislation, being the Sovereign own people and charge through the general will, to legislate for the people themselves. Therefore, this paper aims to examine the definition that the author gives to the legislator, his examples and the real need for the existence of this Legislator. Later, we will examine the usefulness for this recurring role in Rousseau's philosophy.